1999
DOI: 10.1021/cm9805471
|View full text |Cite
|
Sign up to set email alerts
|

Cationic and Anionic Vacancies in the Crystalline Phases of Sol−Gel Magnesia−Alumina Catalysts

Abstract: Magnesium−alumina mixed oxide catalysts at Mg:Al atomic ratios of 3:1, 2:1.8, and 1:2.8 were synthesized by using the sol−gel technique. Dehydroxylation and phase transformations were studied with thermogravimetry. Crystalline structures were measured with X-ray powder diffraction. Position and concentration of anionic and cationic vacancies were obtained by refining crystalline structures with the Rietveld technique. When samples were annealed below 400 °C, boehmite, brucite, hydrotalcite, and glushinskite we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
2
18
0
5
Order By: Relevance
“…With further elevating the calcination temperature, the reduction peak temperatures for both dispersed NiO species and aluminate-like species in TPR profiles increased, implying that the interaction between Ni species and support strengthened with the calcination temperature. On the other hand, the incorporation of divalent Mg ions in the tetrahedral or octahedral sites in c-Al 2 O 3 structure resulted in a decrease in the cationic deficiency of c-Al 2 O 3 , thus stabilizing c-Al 2 O 3 -NiAl 2 O 4 nanoparticles and elevating the reduction temperature of Ni 2+ ions in spinel phase [56]. As a whole, the increase in the reduction peak intensity for aluminate-like species with the calcination temperature suggested that more Ni ions diffused into the lattices of c-alumina to form spinel.…”
Section: Xps Analysismentioning
confidence: 99%
“…With further elevating the calcination temperature, the reduction peak temperatures for both dispersed NiO species and aluminate-like species in TPR profiles increased, implying that the interaction between Ni species and support strengthened with the calcination temperature. On the other hand, the incorporation of divalent Mg ions in the tetrahedral or octahedral sites in c-Al 2 O 3 structure resulted in a decrease in the cationic deficiency of c-Al 2 O 3 , thus stabilizing c-Al 2 O 3 -NiAl 2 O 4 nanoparticles and elevating the reduction temperature of Ni 2+ ions in spinel phase [56]. As a whole, the increase in the reduction peak intensity for aluminate-like species with the calcination temperature suggested that more Ni ions diffused into the lattices of c-alumina to form spinel.…”
Section: Xps Analysismentioning
confidence: 99%
“…In order to modify the textural properties of LDHs and their calcination products, different LDHs have been obtained using the sol-gel method. This includes the hydrolysis of alkoxide precursors and has been used to obtain solids of different nature, including TiO 2 -MgO (18), MgO-Al 2 O 3 (19) and Ga 2 O 3 -Al 2 O 3 (20) systems. This paper reports on the synthesis of Mg/Al, Mg/Ga and Mg/In LDH using the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance the polyol method performed by the hydrolysis of the metal acetate salts in ethylene glycol or di ethylene glycol under heating produces pure acetate intercalated LDH, this in absence of pH and atmosphere control and without an excess of a base (Prevot et al, 2005). Alternatively the sol-gel route in an organic medium yields LDH materials after hydrolysis and condensation polymerization reactions of metal alkoxide precursors (Wang et al, 1999). Of lower relevance for large scale production and from application related aspects, reversed micelles or micro emulsions may be employed to drastically change the LDH platelets morphology into fiber-like particles (Hu & O'Hare, 2005), and a sophisticated method using inverse opals is reported to yield three dimensional ordered macroporous LDH materials, the polystyrene beads based opal array acting as a sacrificial template (Géraud et al, 2006).…”
Section: Layered Double Hydroxides (Ldh)mentioning
confidence: 99%